Między reformami a zmianą systemową w ZSRR/FR - Stępień-Kuczyńska, Alicja (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2020)
W artykule autorka stawia tezę, że w latach pieriestrojki, a następnie pierwszego etapu istnienia Federacji Rosyjskiej, nie zaistniały warunki gospodarcze, społeczne i polityczne dla budowy demokracji. Przyczyny tego stanu rzeczy autorka upatruje w źle przeprowadzonych reformach ekonomicznych, słabości instytucji systemowych, braku konsensusu elit. Istotny, okazał się wysoki poziom inercji społeczeństwa, zwłaszcza po nieudanych reformach pieriestrojki i rozpadzie państwa. Otoczenie międzynarodowe początkowo wspierało, głównie deklaratywnie pieriestrojkę Gorbaczowa, jednakże w wyniku naruszania standardów demokracji przez Jelcyna i jego ekipę, nie sprzyjało w sposób efektywny, procesom demokratyzacyjnym w tym państwie.

The author of the article puts forward a thesis that the economic, social and political conditions at the time of perestroika and, then, in the first period of the Russian Federation were not conducive to the emergence of democracy. In the author’s opinion, this state of affairs is due to poorly carried out economic reforms, weaknesses of systemic institutions, and the lack of consensus among the elites. High levels of public inertia turned out to be essential as well, especially after the failed perestroika reforms and the collapse of the state. The international environment initially supported Gorbachev’s perestroika, albeit mainly verbally. However, after Yeltsin and his team violated democratic standards, this support was ineffective in promoting democratization processes in Russia.
Between Reforms and Systemic Change in the USSR/Russian Federation
Keywords: system polityczny; zmiana; ZSRR; Rosja; political system; change; USSR; Russia